Respiratory morbidity in patients with spinal muscular atrophy—a changing world in the light of disease-modifying therapies - Lagae, Leen; Proesmans, Marijke; Van den Hauwe, Marleen; Vermeulen, François; De Waele, Liesbeth; Boon, Mieke (Frontiers in Pediatrics, 2024)
Respiratory complications are common in spinal muscular atrophy (SMA) and significantly contribute to morbidity and mortality in these patients. Generalized respiratory and bulbar muscle weakness translates into diverse and complex clinical consequences necessitating strict follow-up and specialized care. The natural history of SMA has evolved drastically in recent years as a result of the introduction of novel, disease-modifying therapies. While the impact of these therapies on motor function is well described in literature, its consequence for respiratory management has not been extensively studied.In this review we aim to provide a comprehensive overview of the respiratory morbidities, their followup, management, and the impact of novel therapies in SMA.